1991
DOI: 10.1016/0092-8674(91)90411-q
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of two 85 kd proteins that associate with receptor tyrosine kinases, middle-T/pp60c-src complexes, and PI3-kinase

Abstract: Affinity-purified bovine brain phosphatidylinositol 3-kinase (PI3-kinase) contains two major proteins of 85 and 110 kd. Amino acid sequence analysis and cDNA cloning reveals two related 85 kd proteins (p85 alpha and p85 beta), which both contain one SH3 and two SH2 regions (src homology regions). When expressed, these 85 kd proteins bind to and are substrates for tyrosine-phosphorylated receptor kinases and the polyoma virus middle-T antigen/pp60c-src complex, but lack PI3-kinase activity. However, an antiseru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
439
0
1

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 759 publications
(453 citation statements)
references
References 92 publications
13
439
0
1
Order By: Relevance
“…Induction of p85-associated PI3-K activity in the membrane fraction of T. parva-transformed B cells Class I PI3-K activity can be immunoprecipitated from cell extracts with an antibody directed to its regulatory p85 subunit (Otsu et al, 1991). To address the question as to whether infection leads to modulation of host cell PI3-K activity in the course of Theileria-induced B-cell transformation, we quantified p85-associated PI3-K activity in the membrane fraction of parasitized proliferating B cells and compared it with that observed in drug-cured B lymphocytes (see Experimental procedures).…”
Section: Resultsmentioning
confidence: 99%
“…Induction of p85-associated PI3-K activity in the membrane fraction of T. parva-transformed B cells Class I PI3-K activity can be immunoprecipitated from cell extracts with an antibody directed to its regulatory p85 subunit (Otsu et al, 1991). To address the question as to whether infection leads to modulation of host cell PI3-K activity in the course of Theileria-induced B-cell transformation, we quantified p85-associated PI3-K activity in the membrane fraction of parasitized proliferating B cells and compared it with that observed in drug-cured B lymphocytes (see Experimental procedures).…”
Section: Resultsmentioning
confidence: 99%
“…13, 1993 ificity of P13K for binding sites within certain receptor tyrosine kinases is supported by the derivation of a consensus sequence for sites of interaction with p85a (5) and the demonstration of sequence discrimination by both SH2 domains of p85ot (22,26,38). In addition, the difference in binding specificity between isolated p85 and p85 complexed with p110 has aroused speculation that the p110 subunit of PI3K modulates the binding specificity of the p85 subunit (35). Similarly, alternative expression or assembly of subunits may allow for binding specificity to nonreceptor tyrosine kinases.…”
Section: Discussionmentioning
confidence: 98%
“…It has been suggested that differential expression or assembly of the various P13K subunits may confer binding specificity between receptor tyrosine kinases (22,35). Spec-VOL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 60 sequen~s were extracted from the databank. Seven additional domains (Bovine p85 a andp Nand C.terminal SH2 domains [ 12]; human phosphor yrosine phosphatass (PTP) IC N-and C-termlnal SH2 domains [3]; avian tensln SH2 domain [5]) were obtained from the literature.…”
Section: Introduction Ences May Not Be Made Through Homology Modellinmentioning
confidence: 99%